The Results of Inquiry-Based Learning Management on Critical Thinking and Academic Achievement of Grade-8 Students - Leekhot, Khwanjira; Payougkiattikun, Wisarut; Thongsuk, Tawan (Integrated Science Education Journal, 2024)
Purpose of the Study: The objectives of this research were threefold: (1) to evaluate the analytical thinking ability of Grade 8 students following exposure to the inquiry-based 7E learning model, (2) to assess the academic achievements of these students both before and after engaging in 7E learning, and (3) to explore the students' satisfaction with their learning experience under the 7E framework. Methodology: The study involved 39 Grade 8 students from a school in Kalasin province, selected via Cluster Random Sampling during the first semester of the 2023 academic year. The research utilized a pre-experimental One Group Pretest-Posttest Design, with a classroom as the sampling unit. Data were gathered through pretests, posttests, and satisfaction surveys, with a focus on measuring analytical thinking and academic achievement. Main Findings: The study revealed three key outcomes: (1) Students' critical thinking abilities improved significantly after learning with the 7E model, with results showing a statistically significant difference at the .05 level. (2) Academic achievement post-7E learning was recorded at 70.17%, indicating a notable improvement from the pretest scores. (3) Students reported high satisfaction with the 7E learning experience, emphasizing its positive impact on learning and engagement. Novelty/Originality of this Study: This research contributes uniquely by demonstrating the effectiveness of the 7E inquiry-based learning model in enhancing critical thinking, a vital 21st-century skill. The study also shows how the 7E model boosts student engagement and academic performance, offering an innovative approach to fostering deeper cognitive skills and academic success in a rapidly evolving educational landscape.